Liquid Phase Electron-Beam-Induced Deposition on Bulk Substrates Using Environmental Scanning Electron Microscopy. (3rd March 2014) - Bresin, Matthew; Botman, Aurelien; Randolph, Steven J; Straw, Marcus; Hastings, Jeffrey Todd
Abstract The introduction of gases, such as water vapor, into an environmental scanning electron microscope is common practice to assist in the imaging of insulating or biological materials. However, this capability may also be exploited to introduce, or form, liquid phase precursors for electron-beam-induced deposition. In this work, the authors report the deposition of silver (Ag) and copper (Cu) structures using two different cell-less in situ deposition methods—the first involving the in situ hydration of solid precursors and the second involving the insertion of liquid droplets using a capillary style liquid injection system. Critically, the inclusion of surfactants is shown to drastically improve pattern replication without diminishing the purity of the metal deposits. Surfactants are estimated to reduce the droplet contact angle to below 10°.